Modifikasi fisik tepung suweg (Amorphophallus campanulatus) dengan iradiasi sinar ultraviolet C (UV-C) dan heat moisture treatment (HMT) - Dewi Novita; Umar Hafidz Asy'ari Hasbullah; Fafa Nurdyansyah; Iffah Muflihati (AGROINTEK, 2023)
Suweg (Amorphophallus campanulatus) is a tuber that has not to explored widely for its use. This study aimed to determine the effect of physical modification of UV-C and HMT on the characteristics of suweg flour. This study used a factorial design with two factors. The first factor is the type of modification which consists of Ultraviolet-C Irradiation (UV-C) and Heat Moisture Treatment (HMT). The second factor is the length of modification time. The UV-C modification uses 10 min, 20 min, and 30 min. Simultaneously, the HMT modification uses four, five, and six hours. The control used unmodified suweg flour. The result showed that the modified UV-C and HMT methods with different time-process variations affect the suweg flour characteristics. UV-C and HMT modification was increased solubility and yellowness (b*). In contrast, it decreased yield, moisture content, lightness (L*), and redness (a*). HMT modification had a most significant effect than UV-C modification in suweg flour modification.